Impact of an Educational Program upon Nurses’ Knowledge and Practices Concerning Neurogenic Bladder Rehabilitation for Spinal Cord Injured Persons - badir, Raheem; Jaddoue, Batool (Iraqi National Journal of Nursing Specialties, 2012)
Objectives: To determine the impact of an educational program on nurses’ knowledgeand practices concerning neurogenic bladder rehabilitation for spinal cord injured personsthrough a follow-up approach each two months post program implementation for sixmonths.Methodology: "Follow-up" longitudinal design by using time series approach of dataanalysis and the application of pre-post tests approach for the study and the controlgroups. The study was carried out at Ibn Al-Kuff hospital for (SCI) in Baghdad governoratefrom 5th of July 2010 to 15th of October 2011. To achieve the objectives of the study, anon-probability (purposive) sample of (60) nurses (males and females) were working in SCIunits were selected. The sample is divided equally into study and control groups. Aquestionnaire format was used for data collection which consisted of (3) three parts (185)items, including their knowledge, practices, and demographic characteristics. Instrumentvalidity was determined through content validity, by a panel of experts. Reliability of theinstrument was determined through the use of Pearson correlation coefficient for the testretestapproach, which is (0.92) for their knowledge and (0.88) for their practices. Analysisof data was performed through the application of descriptive statistics (frequency,percentage) and inferential statistics (mean of scores, relative sufficiency, Pearsoncorrelation coefficient, t-test and one way analysis of variance and chi- square test).71Iraqi National Journal of Nursing Specialties, Vol. 25 (2) 2012Results: The results of the study indicated that the nurses in study group benefited fromthe implementation of health education program, their knowledge and practices wereadequately improved and developed.Recommendations: The study recommends that there is a need to conduct annualexaminations for nurses to evaluate their nursing care for SCI persons, with a focus on thepractical side, and not upgrading any of them if they did not pass the examinationsuccessfully.